Proses Revisi Muatan MT. Meghna Pride Pada PT. Samudera Sarana Karunia Dumai - M. Althariq; Syarifur Ridho; Suratni Ginting (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to identify the factors that hinder the use of the customs manifest application, the impacts caused, and the efforts made by PT. Samudera Sarana Karunia in overcoming the issues encountered. The research employs a qualitative descriptive method to provide an in-depth explanation of the influence of the customs manifest application on the inward & outward issuance process within the company. Data collection techniques include observation, interviews, documentation, and literature studies.The study results indicate several factors that affect the use of the customs manifest application in the inward & outward issuance process. These factors include the absence of dedicated staff assigned to operate the application, restricted access as the application can only be operated via computer, and the lack of operational flexibility in using the application. These limitations lead to several impacts, such as errors in data entry, the absence of backup devices in case of a system failure, and restricted mobility due to the fixed nature of desktop computers.To address these issues, PT. Samudera Sarana Karunia has undertaken several efforts, including training operational staff to improve their proficiency in using the application, proposing a transition from desktop computers to laptops to enhance work flexibility, and holding regular coordination meetings among operational staff to ensure the smooth implementation of the customs manifest application. Through these measures, the company aims to minimize existing obstacles and improve the efficiency of the inward & outward issuance process.